Jornalismo, ironia e informação - Vianna, Rodolfo (2011)
The hypothesis of this research is to understand the presence of irony in the informative journalistic genre as enabler of the reader‟s inference, an indirect argument that values positively or negatively what is being informed and/or the sides involved in the events reported. Firstly, I sought to comprehend the informative journalistic genre macro-features from the standpoints of the Bakhtin Circle formulations and analyzing the Style Guide of the newspaper from this research corpus (Folha de S. Paulo). In a second step, I delimited an understanding of what would be irony from a dialogue with three authors whose works on the theme: Alain Berrendonner, Linda Hutcheon and Beth Brait. Irony can be briefly taken as argumentative ambiguity, result of the addressee/reader‟s inference, whose chances of concretization involves the linguistic, enunciative and discursive plans. The ironic manifestations are also studied in the light of the informative journalistic genre requirements and of the characteristic verbal-visual composition of the printed newspaper pages. The corpus is composed of the material collected over one week of the Folha de S. Paulo newspaper (from 06/29/2009 to 07/05/2009). This newspaper was chosen because it had the largest daily nationwide circulation average in 2009. I only analyzed the news that fit the informative journalistic genre, thus excluding opinative texts and images (editorials, feature articles, analysis, interviews, cartoons, etc.). The analysis allowed building two large recurrences of irony as the hypotheses of this research: the ambiguity of the quotation marks use (autonymy / autonymous modalization) and the ironic articulation between image and text. The desired contribution, both for Applied Linguistics as for the Language Studies in general, is to show that even the journalist discourse, which is apparently guided by the objectivity, is subjected to socio-cultural and historical conditions and that can be observed, for example, through the manifestation of the ironic phenomenon